The Incidence Rate of Central Nervous System (CNS) Involvement in Pediatric Patients Diagnosed with Lymphoblastic Leukemia (ACUTE) - Shagufta Shoukat, Muhammad Adil, Naheeda Tareen, Altaf, Tariq Ali, Sandeep Kumar (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: The objective of this study is to establish the incidence rate of central nervous system (CNS) involvement in pediatric patients diagnosed with lymphoblastic leukemia (acute). Methodology: A cross-sectional survey was undertaken in the Paediatric Oncology Unit, Sheikh Khalifa Bin Zayyed Hospital, Quetta hospital between 12th January 2021 and August 2022. This research study included 115 patients who fulfilled the eligibility criteria. Demographic profiles were recorded including age, gender and address. Lumbar puncture was done by a single doctor in all these patients at diagnosis to look for CNS involvement. CSF examinations of all patients were done by a single laboratory. Results: The patients had a mean age of 5.9±3.3 years, and the study consisted of 46 (40%) female and 69 (60%) male participants. There were 6 (5.2%) patients who had CNS involvement and 109 (94.8%) had no CNS involvement. In the age range of 1-5, 6-10 and 11-15 years, there were 2 (1.7%) patients who had CNS involvement respectively. In the stratification of CNS involvement with gender, in male patients, there were 2 (1.7%) patients who had CNS involvement and in female patients, there were 4 (3.5%) patients who had CNS involvement. Conclusion: In conclusion, this study reveals that central nervous system involvement in children with acute lymphoblastic leukemia is prevalent upon initial diagnosis. Nevertheless, some disparities have been observed from Western data, such as dissimilarities in age distribution. Keywords: nervous system, Acute lymphoblastic leukemia, white blood cells, total leucocyte counts.